(untitled) (American Journal of Islam and Society, 1995)
John Waller, an American foreign service officer and retired inspector general of the CIA, is now an independent writer based in McLean, Virginia. He is also the author of Gordon of Khartoum and has travelled extensively in the Middle East and Asia. The book is beautifully illustrated with photographs of men, women, and events of the time, which succeed in invoking visually the time period with which he is dealing: the First Afghan-British War. This thirty-chapter book is the story of the British failure in Afghanistan in the 1840s, as Britain competed with Czarist Russia for strategic advantage in Central Asia. Beyond the Khyber Pass is a sweeping saga, chronicling the brutal wars and international intrigues of the nineteenth century in India, Afghanistan, Central Asia, and Russia-the "Great Game" that culminated in the siege of Kabul and the massacre of sixteen thousand British soldiers, their families, and camp followers in 1842, the year of the First Afghan-British War. Waller tells the tale of intrigue, treachery, and wild adventure with relish evident in the juicy anecdotes and asides ...